Measuring Customers' Perceived Service Quality in Hotel Industry - Md. Sidin, Samsinar; Abdul Rashid, Md. Zabid; Raja Zainal, Raja Anis Rahyuwati (Universiti Putra Malaysia Press, 2001)
This research attempts to study customer's perceived se",ice quality in the hotel industry. This paper aims to discover what customers think of the quality of service as can be found in the hotel industry by looking into factors influential on this perception such as personal service, technological innovations and quality of food served. The method employed to gather the research resources was adopted from SERVQUAL which is a popular method in measuring perceived service quality. The descriptive and inferential methods were also used in testing and analysing the hypotheses. Data were analysed by using the SPSS package. The research findings indicated that generally, customers were dissatisfied with the service quality provided by the hotel management. From the research, it was also discovered that personal services technology innovation and quality of food served were vital in improving customers' outlook on the service quality. Therefore, the hotelier should try to meet or exceed the customers' expectations, in order to ensure the customers are satisfied. It is very important for the hotelier to take an effort in comprehending and understanding customers' expectations in order to deliver good service, in which if the perceived service equal or exceeded the expected service, they perceived that there is a quality in the service.